(untitled) (Global Journal of Science Frontier Research, 2017)
Glyphosate (Tiller 480 SL), which is used extensively to control and inhibit weeds in terrestrial and aquatic ecosystems, has been blamed of harming non-targeted species like fish. This current study evaluated the acute and chronic impacts of glyphosate on the Arabian killifish (Aphanius dispar) collected from Southwestern Saudi Arabia at different levels of biological organization including behavioral and histopathological responses. Glyphosate toxicity (96 h LC50) to Aphanius dispar was determined at 115.25 mg/l after exposure to 60, 90, 120, 150, 180, 210, 240 mg glyphosate/l. Fish during the 96 h displayed abnormal behavioral changes: erratic movements, hyperactivity, rapid opercula and mouth movements, surfacing, hypoactivity, exhaustion and mortality. While, exposure of fish to 1/4th of the 96-h LC50 for two weeks, the gills and liver organs displayed histopathological alterations.